Critical approaches to TV and film set design - D'Arcy, Geraint (Routledge, 2019)
"The analysis of scenic design in film and television is often neglected, with visual design elements relegated to part of the mise-en-scene in cinema or simply as 'wallpaper' in television. Critical Approaches to TV and Film Set Design, positions itself from the audience perspective to explore how we watch TV and film, and how set design enhances and influences the viewing experience. By using semiotics, history and narratology and adding concepts drawn from art, architecture and theatre, Geraint D'Arcy reworks the key concepts of set design. Looking at the impact of production design on how the viewer reads film and television, these updated theories can be applied more flexibly and extensively in academic criticism. D'Arcy creates a new theoretical approach, representing a significant expansion of the field and filling the remaining gaps. This book is ideal for anyone interested in understanding how we can read and interpret design in film and television, and should be the primary point of reference for those studying TV and film set design"--